Water rise in the xylem of plants with tracheidal conductance - Iosif Anshelevich Kipnis; Yury Mikhaylovich Vernigorov (Advanced Engineering Research)
The work objective is a water movement modeling in the plant xylem allowing for the hydraulic loss on a single bordered pit torus, as well as on the pore population. However, as it follows from a number of publications, root pressure is not a mechanism providing water rising in plants. A model representation is based on the assumption that the main reason for rising water in plants is the surface tension in the meniscus of the xylem capillary. At this, it is necessary to take into account the xylem structure features of the needle-leaved and broadleaved trees. The equation to calculate the water rise in the xylem capillary of plants with tracheidal conductance is derived with account for the anatomy structure of the tracheids and bordered pores. The equation allows determining the change in the hydraulic losses in the movement of water through a single bordered pore and through the pore population taking into account the orientation of the latter. The model allows calculating the height of the water rise in the xylem capillary. It is shown that an increase in the diameter of the tracheid cavity and in the diameters of the bordered pore and torus, ceteris paribus leads to the rising of the hydraulic losses.